Intra-abdominal recurrence from colorectal carcinoma: Differences and similarities between local and peritoneal recurrence. (March 2020) - Dumont, Frédéric; Joseph, Solène; Lorimier, Gérard; De Franco, Valéria; Wernert, Romuald; Verriele, Valérie; Kerdraon, Olivier; Campion, Loic; Capitain, Olivier; Guerin-Meyer, Véronique; Raimbourg, Judith; Senellart, Hélène; et al.
Abstract: Background: Peritoneal recurrences from colo-rectal cancer can be isolated (PR) or associated with local recurrences (LR). The purpose of this study was to analyze patterns and outcomes of LR and PR. Methods: Analyze from a prospective database of 108 patients treated with CCS plus HIPEC at two cancer centers between 2008 and 2015. Results: The population was divided into an LPR group (presence of LR with or without PR, n = 56) and a PR group (isolated PR, n = 52). The patients characteristics (age, sex, Charlson score, PCI) or perioperative treatments were comparable between the groups. The median number of resected organs for tumor involvement (respectively, 2 vs 1; p < 0.001), the percentage of patients with metastatic lymph nodes (LN+) from the resected specimen (respectively, 25% vs 7%; p = 0.016) and the mortality rate (respectively, 9% vs 0%; p = 0.023) were significantly higher in the LPR group. After a median follow-up of 32 (1–108) months, median overall survival was comparable between the two groups (respectively, 46 vs 42 months; p = 0.262). Conclusions: LR is associated with a higher incidence of organ invasion, LN involvement (25%) and postoperative mortality. Optimal surgical resection of LR with systematic lymphadenectomy of invaded organs seems mandatory. Highlights: Local and peritoneal recurrence from colorectal cancer are two differents disease. Local recurrence involve more frequently adjacent organ. Lymph node spreading rate is higher in local recurrence. Mortality rate is higher in local recurrence. Survival is similar between local and peritoneal recurrence.